The Implication of Social Media Marketing in the Education Sector: Evaluating the Impact of Social Media-Induced Marketing Elements on Brand Engagement - Kiran, Ram (Global journal of Business and Integral Security, 2024)
The education sector has witnessed significant growth with multiple tech firms that engage in providing services to students. Such services need to be promoted in order to increase the level of awareness among students and attract more students to avail of such services. However, students from a unique demographical community and such aspects need to be considered in order to develop a strategic social marketing plan. The purpose of the current study is to conduct an empirical analysis of how education brands in the education sector utilise social media marketing in order to increase the level of awareness and level of student engagement with the brand. This purpose has been addressed in the current study by collecting data and conducting empirical analysis with 250 different students who are part of different educational institutions and take services from education sector firms. Empirical analysis conducted in the current study has suggested student perception, brand loyalty, brand equity, and the level of student engagement does influence the expected performance of social media marketing campaign conducted by education brands. Education brands are required to ensure that they develop a positive level of student perception, engagement, brand loyalty and trust in order to attract more students to utilise their service amidst growing competition in this sector which is witnessing the growth of several edtech firms who attempt to engage and occupy larger student share in social media platforms. The current study is a novel attempt to establish strategies which can be adopted for improving the effectiveness of marketing campaigns.